(untitled) (Palíndromo, 2022)
From four pieces in micro mosaic from the Ferreira das Neves collection of the Museu D. João VI-EBA-UFRJ, the proposal of this article approaches the analysis of the technique, of their image-form, historicity and collecting process, the identification of their origin and date, the theoretical-methodological paths involved in the research and the reflections instigated by the aesthetics of tiny things, in which the gaze is unavoidably related to proximity and detail. In this sense, we seek to present the importance of tiny things for art historical narratives and their particular aesthetic potency.